Stress Analysis of Semi-covered Excavation Foundation Pit in Metro Stations based on Incremental Method - Qin, Xuebo; Jiang, Aici; Wei, Zhongao (Transactions on Environment, Energy and Earth Sciences, 2024)
The station foundation pit of Ningbo Metro Line 2 is taken as engineering background, the support structure form of the semi covered excavation foundation pit is introduced. The standard section of the foundation pit is considered as a plane strain problem, a force calculation and analysis model for the half cover system structure is established based on the incremental method, concentrated load of a waste truck is applied within 5.0 m cover plate range outside the middle column and an impact coefficient of 0.4 is considered, overload with value of 20kPa is applied to the rest parts of the cover plate and 5.0 m outside the diaphragm wall. The excavation of the foundation pit is divided into 5 stages, the surface overload, structural self weight, soil pressure and elastic resistance increment, and support axial force are applied respectively, and the bending moment increment of the connecting wall and cover plate system at each excavation stage are calculated. The bearing capacities of the diaphragm wall and cover plate reinforcement are respectively calculated based on the rectangular bending normal section components, and they both meet the strength requirements.